2022
DOI: 10.1111/nyas.14846
|View full text |Cite
|
Sign up to set email alerts
|

Sawing the branch of near‐death experience research: A critical analysis of Parnia et al.’s paper

Abstract: In their recent paper, Parnia and colleagues propose a new label for the near-death experience (NDE): recalled experience of death. They claimed NDEs are "authentic" only when an objective danger is present and that authentic NDEs have a proven core phenomenology. We consider that these claims are insufficiently supported by empirical data. NDEs appear as a continuum of heterogeneous experiences of consciousness precipitated by the disjunction of processes usually combined in normal mental activity. The "core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This NDE definition opens the door to the understanding of NDEs via the knowledge of the neurophysiological bases of the generation of wakefulness and awareness and of changes in these basic attributes of consciousness (e.g., Sperry, 1968 ; Crick and Koch, 1990 ; Edelman, 1992 ; Baars, 1993 ; Aru et al, 2012 ; Damasio, 2012 ; Dehaene, 2014 ; Tononi et al, 2016 ; Gazzaniga, 2018 ; Ehret and Romand, 2022 ). The definition of an authentic NDE or RED by listing necessary presence and absence of components in the NDE reports has been criticized ( Evrard et al, 2022 ) as “ a very risky strategy, which truncates the NDE phenomenon to avoid confronting what the last decades of research have revealed.”…”
Section: How Have Near-death Experiences Been Defined?mentioning
confidence: 99%
“…This NDE definition opens the door to the understanding of NDEs via the knowledge of the neurophysiological bases of the generation of wakefulness and awareness and of changes in these basic attributes of consciousness (e.g., Sperry, 1968 ; Crick and Koch, 1990 ; Edelman, 1992 ; Baars, 1993 ; Aru et al, 2012 ; Damasio, 2012 ; Dehaene, 2014 ; Tononi et al, 2016 ; Gazzaniga, 2018 ; Ehret and Romand, 2022 ). The definition of an authentic NDE or RED by listing necessary presence and absence of components in the NDE reports has been criticized ( Evrard et al, 2022 ) as “ a very risky strategy, which truncates the NDE phenomenon to avoid confronting what the last decades of research have revealed.”…”
Section: How Have Near-death Experiences Been Defined?mentioning
confidence: 99%
“…Sometimes during real or presumed life-threatening and/ or near-death circumstances, an individual undergoes an altered state of consciousness technically referred to as a near-death experience (NDE), which has been reported by around 4% to 8% of the adult population (Greyson, 1993b;Knoblauch et al, 2001;Perera et al, 2005). Although there are still some disagreements on defining the NDE (Evrard et al, 2022;Long, 2014;Martial et al, 2022;Parnia et al, 2022;Romand & Ehret, 2023;van Wees et al, 2011), the Near-Death Experience Research Foundation defines it as "a lucid experience associated with perceived consciousness apart from the body occurring at the time of actual or threatened imminent death" (Long, 1999). As aptly pointed out in that definition, the typical NDE is most often associated with the perception of a separation from the physical body, but it also might include perceptions of darkness or light, alterations of time, feelings of calm or peace, encounters with presumed NDE personages, visual life reviews, or various other features (Greyson, 1983b;Greyson & Stevenson, 1980;Martial et al, 2017Martial et al, , 2020Moody, 1976;Ring, 1980;Sabom, 1982).…”
mentioning
confidence: 99%